Exchange-project: images of history in Bulgaria and Austria - Dyballa, Jacqueline (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2022)
This article presents an intercultural and interdisciplinary exchange project for German language and literature students at Sofia University and history students at Alpen-Adria University Klagenfurt. Starting with a brief description of the role of one’s own historical consciousness in foreign language teaching, the project is discussed. Afterwards, the goals and the process of the project History Images in Bulgaria and Austria will be described. The project is then evaluated from the point of view of some of the students, based on reports of their experiences and their results. The paper aims to encourage similar international projects in German studies abroad.
Keywords: оnline language project; history images; intercultural exchange